3D Imaging and Organoid Bioprinting - Sandesh Narayan Somnache; Amisha S Raikar (German Journal of Pharmaceuticals and Biomaterials, 2024)
Three decades ago, Charles Hull laid the foundation for 3D bioprinting by initiating a mechanical procedure intended for the fabrication of solid scaffolds. Since then, this field has evolved significantly, transforming into a promising technique for precisely depositing biological substances, living cells, and growth factors to generate bioengineered constructs through computer-assisted deposition and assembly methods.